Does trauma-focused exposure therapy exacerbate symptoms among patients with comorbid PTSD and substance use disorders? - Lancaster, Cynthia L. (Behav Cogn Psychother, 2019)
BACKGROUND: Although exposure-based therapy is a well-established, effective treatment for post-traumatic stress disorder (PTSD), some practitioners report reluctance to implement it due to concerns that it may exacerbate symptoms of PTSD and commonly comorbid disorders, such as substance use disorders (SUD). AIM: This study compared the exacerbation of psychological symptoms among participants with comorbid PTSD and SUD who received either SUD treatment alone or SUD treatment integrated with exposure therapy for PTSD. METHOD: Participants (N = 71) were treatment-seeking, military Veterans with comorbid PTSD and SUD who were randomized to 12 individual sessions of either (1) an integrated, exposure-based treatment (Concurrent Treatment of PTSD and Substance Use Disorders using Prolonged Exposure; COPE); or (2) a non-exposure-based, SUD-only treatment (Relapse Prevention; RP). We examined between-group differences in the frequency of statistically reliable exacerbations of PTSD, SUD and depression symptoms experienced during treatment. RESULTS: At each of the 12 sessions, symptom exacerbation was minimal and generally equally likely in either treatment group. However, an analysis of treatment completers suggests that RP participants experienced slightly more exacerbations of PTSD symptoms during the course of treatment. CONCLUSIONS: This study is the first to investigate symptom exacerbation throughout trauma-focused exposure therapy for individuals with comorbid PTSD and SUD. Results add to a growing literature which suggests that trauma-focused, exposure-based therapy does not increase the risk of symptom exacerbation relative to non-exposure-based therapy.